Strategic Vertical Separation - Igor Sloev (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
The paper explores incentives for strategic vertical separation of firms in a framework of a simple duopoly model. Each firm chooses either to be a retailer of its own good (vertical integration) or to sell its good through an independent exclusive retailer (vertical separation). In the latter case a two-part tariff is applied. Retailers compete in quantities, goods are perfect substitutes and firms' cost functions are quadratic. I show that the equilibrium outcome crucially depends on the degree of (dis)economies of scale and asymmetry of costs. Two asymmetric equilibria arise, in which one firm separates while another integrates, under conditions that both firms' cost functions exhibit a sufficiently high diseconomies of scale, or extreme asymmetry of costs. Under a moderate asymmetry of costs a unique equilibrium exists in which the firm with the lower degree of diseconomies of scale separates, while its rival integrates. With the degree of diseconomies of scale low for both firms in the unique equilibrium both firms separate.
urn:nbn:de:bvb:19-epub-13258-2
Keywords: L22; L42; 330; Vertical oligopoly; Vertical Separation; Vertical Integration; Delegation; Vertikale Integration; Make-or- Buy-Entscheidung; Einzelhandel; Duopol; Theorie